Mekanisme Penyebaran Cacar Monyet dan Faktor-Faktor Yang Mempengaruhinya - I Ketut Suarayasa; Zulkifli; Ofel mazmur Kristoper (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Introduction: On May 29, 2022, the World Health Organization (WHO) described the global public health risk from multi-country monkeypox outbreaks in non-endemic countries as "moderate." WHO pointed out that "this is the first time that cases and groups of monkeypox have been reported simultaneously in very different geographic areas and with no known epidemiological link to endemic countries". On 7 May 2022, England confirmed a case of monkeypox. Their report marks the start of the detection of the rapid and unprecedented global spread of the virus, featuring human-to-human and community transmission. Approximately one month later, confirmed cases of monkeypox rose to 3,453 in at least 55 non-endemic countries, covering every continent other than Antarctica. Objective: To know the mechanism of the spread of monkeypox and the factors that influence it. Results: Based on several kinds of literature, shows the spread of the monkeypox virus starts from travelers to endemic areas so currently there are many cases of monkeypox found in non-endemic areas. Factors that influence the spread of the disease with the highest presentation are associated with a history of sexual contact where the highest proportion occurs in MSM (men who have sex with men), followed by droplet exposure and direct contact with lesions on the patient's skin.